Inconsistent definitions of money and currency in financial legislation as a threat to innovation and sustainability - Leander Bindewald (Journal of Risk and Financial Management, 2021)
External shocks, like the climate catastrophe or the COVID-19 pandemic, as well as intrinsic fallacies like the securitization of bad debt leading up to the financial crisis in 2008, point to the need for updating our monetary and financial systems. Ensuring their adequacy and resilience is an important factor for sustainability at large. This paper examines the definitions of "money" and "currency" in financial legislation as a foundational factor in achieving systemic resilience by allowing or hampering monetary innovation and diversity. From the unencumbered vantage point that the practice of complementary currencies offers, definitions of the terms "money" and "currency" are here traced through the laws and regulations of the United States of America, from the beginnings of modern banking to the recent rulings on crypto-currencies. They are both found to be used and defined in contradictory ways that are inapt even in regard to conventional modern banking practices, let alone when applied to novelty in payment, issuance and valuation. Consequently, this paper argues that basic legal definitions need to be reviewed and consolidated to enable the innovation and diversification in monetary systems needed for long term macro-economic stability. With this in mind, a terminology that is consistent with monetary practice-current, past and future-as well as the procedural difficulties of reforming laws and regulations is proposed.
Keywords: 330; complementary currencies; financial regulation; legal analysis; monetary theory; systemic sustainability